Hungarian Monitoring, 1 August 1990 . [Magyar rádiófigyelő], 1990. augusztus 1 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Danube-Adriatic summit - Shevardnadze-Baker meeting - Split in the Polish Solidarity movement - Civil war in Liberia Domestic Affairs: - New chief military prosecutor - Canadian army chief of staff in Budapest - Pozsgay on the failed referendum - Comecon market closed in Szeged - Two new crossing points on the Austrian border Economy: - Drastic price increases - Reducing the dominance of the state in the economy - Stagnation in the newly reopened stock exchange - National Interests Negotiation Council (OÉT) agreement on increasing the minimum wage Külpolitika: - Duna-Adria csúcsértekezlet - Sevardnadze-Baker találkozó - Szakadás a lengyel Szolidaritásban - Polgárháború Libériában Belpolitika: - Új katonai főügyész - Budapesten a kanadai hadsereg vezérkari főnöke - Pozsgay a kudarcba fulladt népszavazásról - KGST-piac bezárása Szegeden - Két új átkelőhely az osztrák határon Gazdaság: - Drasztikus áremelkedések - A gazdaság állami túlsúlyának csökkentése - Pangás az újranyitott tőzsdén - OÉT megállapodása a minimálbér növeléséről